Selected health and social needs resulting from state of health of disabled rural inhabitants from the aspect of problems with defining disability - Barbara Kołłątaj (Kazimierz Wielki University, 2020)
Introduction The state of health of an individual and the population depends on many factors, their number and type constituting a specific background of consequences which model the level of health. Human health status is determined by so many factors that despite many scientific studies, also from philosophical aspect, to-date an unequivocal determination of the term - health has not been possible. A similar situation concerns the defining of disease and states of disability. Determination of the dimensions of disability in this respect should be based on a long-term, multi-stage prospective population epidemiological studies, with consideration of constantly performed corrections in order to specify health and social needs. Place of residence, i.e. rural or urban area, is one of the factors which condition the state of health of an individual and the population. Objective The aim of the study was presentation of the most important medical and social problems resulting from the state of health of adult disabled persons living in rural areas from the aspect of defining disability. The main goal was pursued based on two sources of results of research, the first of which were the results of a study conducted within the system of statutory research at the Chair and Department of Epidemiology, Medical University in Lublin. The other source were the results of studies published by other researchers concerning the discussed problem. Selected results of own study and studies by other researchers The article presents the selected results of studies which constitute a certain type of a compendium of scientifically documented problems of the disabled, with particular consideration of such characteristics as: place of residence, causes of disability, objective and subjective state of health, health and social needs. On the level of organization of some studies the dimensions of disability were also considered in rural settlements, communes and provinces. In 1987-1990, a study of the disabled was carried out by a team of researchers from the Institute of Rural Health in randomly selected rural areas of agricultural and industrialized character. Parallel to the above-mentioned study, a comprehensive, all-Polish research of the state of health of rural population was conducted at the Institute of Rural Health. Among the many goals of these studies was the assessment of the state of health and determination of medical and social needs of the disabled. In order to perform a reliable and valid evaluation for the qualification of the examined population of the disabled a 5-degree scale of medical epicrisis was developed. A relatively large research task concerned the epidemiological trends in the occurrence of chronic diseases and the size of disability in Poland during 1990-2006. Own research instruments and data from the reports by the Main Statistical Agency (GUS) and other institutions were used for analysis. The subsequent research task concerned analysis of the selected epidemiological characteristics of disability in Poland and their importance for health care organizations. Patients in hospital wards were examined, as well as primary health care units, specialist outpatient departments, residential homes and occupational therapy workshops. The main aim of the next research task (2013-2015) was determination of the trends in the occurrence of the most important problems of the disabled, according to the cause of disability, as well as the importance of the obtained study results for health care organizations and health policy in the Lublin Province. Also, Lech Panasiuk dealt with the selected characteristics of the state of health of rural inhabitants, and performed analysis of the most important medical and social problems of adult inhabitants of the Lublin Province. The results of studies published by other Polish and international institutions were also presented. Summary and conclusions Similar to many countries, the percentage of the disabled in Polish society is determined in terms of estimates. The main reason for such a situation is the lack of uniform methods and principles of qualification of persons into the group of the disabled. The greatest problems of the disabled living in rural areas include multimorbidity, lack or insufficient provision of rehabilitation, orthopaedic equipment and technical aids, loneliness and various forms of discrimination. It is necessary to carry out multi-thematic health education addressed to rural inhabitants, both the disabled and healthy. Great hopes for improving the quality of life of people with disabilities are connected with the philosophy of the International Classification of Functioning, Disability and Health. To-date, this is the only classification addressing the need for unification of the assessment of the state of health, with consideration of the environment where the disabled person lives, and evaluation of this person's potential. Similar to earlier Classifications and definitions, the ICF is a 'live' classification because efforts are still continuing to make it more comprehensive and detailed.